Legal garantees for e-certification service providers - Labiod, Faiza (Journal of Human Sciences, 2023)
Trust and security are assential elements that must be available in electronic transactions,and achieving this requires the intervention of a third party known as the provider of electronic certification services ,whose task is to certify the data exchanged over the internet ,which leads to authentification of its issuance from the NSBT to it without distortion oral alternative.His success in doing so depends on the performance of the duties imposed on him by law , the violation of which entails his responsibility.However ,the large number and growth of electronic transactions ,and the emergence of new services on the network ,made the current guarantees insufficient to confront modern electronic services , which requires the intervention of the Algerian legislator to organize these services within legal texts ,while determining and controlling the obligations and responsibilities of the certification body in accordance with and the levels of these services.